Notes on Late-glacial retreat of the Antarctic Ice sheet and Holocene environmental changes along the Victoria land coast. - BARONI, CARLO (Institute of Polar Research (Japan), 1994)
Distinct recessional phases with minor readvances of the outlet glaciers in Victoria Land are documented during Late Glacial times when the Antarctic Ice Sheet and its fringing ice shelves receded from the continental shelf in the Ross Sea embayment. Abandoned penguin rookeries supply data both on the history of the glacial retreat that followed the LGM and environmental changes during the Holocene. These were found along the Victoria Land coast and supplied more than seventy 14C dates as old as 13070±405 14C yr B.P. (GX-18483). Marine ingression and the glacio-isostatic uplift ofthe coastal areas that led to the formation ofHolocene raised beaches accompanied deglaciation. Several 14C dates obtained from shells collected in raised marine sediments and from fossil rookeries resting on the raised beaches constrain a relative sea-level curve for the centraI part of Victoria Land. Penguins are sensitive to changes in Antarctic climate and to the environmental parameters that determine their presence and distribution that seemto have changed many times during the Holocene in the Ross Sea. Holocene glacier variations in the Terra Nova Bay area are documented for outlet and local glaciers as well as for ice shelves.